Pengembangan Buku Ajar Mata Kuliah Pendidikan Kesehatan Sekolah bagi Mahasiswa Program Studi Pendidikan Jasmani Universitas Muhammadiyah Kotabumi - Malasari, Citra Azhariat; Suhariyanti, Mela; Fadiah, Kamilah Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to produce a textbook for school health education courses for FKIP UMKO physical education study program students. The research method used is the Borg and Gall development procedure, which consists of 10 steps. However, in this development research, the research does not use all of them, only using seven steps: needs analysis, product creation, product validation, small group trials, stage I product revision, large group trials, and stage II product revision. The product produced is the result of material expert validation with an overall average validation result of 88.91%, the result of media expert validation with a percentage of 90.74%, the result of phase I (small group) trial assessment with a percentage result of 86.50%, and results from the phase II trial assessment (large group) with a percentage result of 91.22%. In conclusion, the development of school health education textbooks for students of the FKIP UMKO physical education study program has developed a textbook product that students in school health education courses can use. Keywords: Textbooks, school health education